Improving Mice's Memory Using the Eight Arm Radial Maze Method Using N- Hexane and Ethanol Extracts of Mustard Green Leaves (Brassica juncea L) - Yusuf, Mashuri; Wati, Apriliana Widya (RADINKA JOURNAL OF HEALTH SCIENCE, 2025)
This research was motivated by whether the n-hexane extract and ethanol extract of the mustard leaf (Brassica juncea L) can affect the memory of male white mice using the eight-arm radial maze method. The objectives of this study were (1) to prove the effective dose of n-hexane extract of mustard greens (Brassica juncea L) leaves to improve the memory power of male white mice. (2) proved the effective dose of ethanol extract of chicory leaves (Brassica juncea L) to improve the memory power of male white mice. (3) determine the most effective dose of the extract to increase the memory power of male white mice. The sample of this study was fresh green mustard leaves. Mustard greens (Brassica juncea L) were determined first. Furthermore, fresh green mustard leaves were divided into two equal parts to be extracted separately using maceration methods with different solvents. The memory test used the eight-arm radial maze method using eight experimental groups with three replications. The results showed that the n-hexane extract of mustard greens, which had an effect on increasing the memory of the mice tested, was omega 3 and omega 6. The most effective dose of the extract to increase the memory power of male white mice was a dose of 2 n-hexane extract in the P3 group.